Cultivation of Family Medicinal Plants (Toga) to Increase Family Income in Tempuran Village, Kec. Suko District. Mojokerto - Indi Nuroini; Enny Istanti (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Cultivation of toga plants is expected to be able to increase people's income and add to the village treasury. To achieve the expected goals, the community service program in Tempuran Village is carried out by empowering the community through socialization of the benefits and procedures for planting toga and getting used to disposing of trash in its place. The people of Tempuran village are still unable to utilize vacant land, litter and discipline the younger generation. Based on the discussion, it can be concluded that the number or amount of community enthusiasm in attending the socialization program carried out during this community service program. Elementary and Kindergarten children are also enthusiastic to take part in competitions and community service as well as morning exercises in this community service work program. Suggestions are that the community is expected to take advantage of the empty land in their home environment to grow medicinal plants and ornamental plants, the community is expected to be able to maintain the cleanliness of the environment by not littering and the younger generation maintains a mutual cooperation attitude which is a reflection of the nation's personality.